2014
DOI: 10.3389/fpsyt.2014.00097
|View full text |Cite
|
Sign up to set email alerts
|

Network Based Statistical Analysis Detects Changes Induced by Continuous Theta-Burst Stimulation on Brain Activity at Rest

Abstract: We combined continuous theta-burst stimulation (cTBS) and resting state (RS)-fMRI approaches to investigate changes in functional connectivity (FC) induced by right dorsolateral prefrontal cortex (DLPFC)–cTBS at rest in a group of healthy subjects. Seed-based fMRI analysis revealed a specific pattern of correlation between the right prefrontal cortex and several brain regions: based on these results, we defined a 29-node network to assess changes in each network connection before and after, respectively, DLPFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Numerous studies, however, have identified opposite rTMS effects across the cortex. While some groups found decreased activity after stimulation (Andoh, Matsushita and Zatorre 2015;Mastropasqua et al 2014;Rahnev et al 2013;Valchev et al 2015;Van Der Werf et al2010;Watanabe, Hanajima, Shirota, Tsutsumi et al 2015), others reported increased brain activity after TMS (Cocchi, Sale, Gollo et al2016;Cocchi, Sale, Lord et al 2015;Eldaief et al 2011;Gratton et al 2013;Manciniet al 2017;Watanabe, Hanajima, Shirota, Ohminami et al 2014). In summary, the inhibitory effect of low-frequency stimulation seems not to generalize from motor to other functional areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies, however, have identified opposite rTMS effects across the cortex. While some groups found decreased activity after stimulation (Andoh, Matsushita and Zatorre 2015;Mastropasqua et al 2014;Rahnev et al 2013;Valchev et al 2015;Van Der Werf et al2010;Watanabe, Hanajima, Shirota, Tsutsumi et al 2015), others reported increased brain activity after TMS (Cocchi, Sale, Gollo et al2016;Cocchi, Sale, Lord et al 2015;Eldaief et al 2011;Gratton et al 2013;Manciniet al 2017;Watanabe, Hanajima, Shirota, Ohminami et al 2014). In summary, the inhibitory effect of low-frequency stimulation seems not to generalize from motor to other functional areas of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies showed coherent findings, i.e. increased FC within the frontal hub of the FPN after excitatory TMS [50], and reduced FPN after inhibitory TBS [54], while the others did not report differences in FPN connectivity after TMS/TBS [49, 51], or reported an inverted direction of effects (i.e., increased FC after inhibitory or decreased FC after excitatory TBS) [52, 53]. Similarly, Eldaief et al [60] using rs-fMRI at baseline to identify individual DMN parietal targets, reported opposite effects according to the frequency of TMS: low-frequency stimulation increased DMN FC, while high-frequency stimulation decreased it [60].…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%
“…Three studies used TMS [49-51] and 3 TBS [52-54] to stimulate the DLPFC. Two studies showed coherent findings, i.e.…”
Section: Local and Distal Connectivity Effects Of Nibsmentioning
confidence: 99%
“…Previous research has shown that repetitive TMS of the DLPFC can alter functional connectivity patterns of the target region with other cortical areas (e.g., the insula, cingulate, parietal and frontal cortices), as well as with deep regions including the striatum and the hippocampus, during resting-state Esslinger et al, 2014;Gratton et al, 2013;Iwabuchi et al, 2017;Mastropasqua et al, 2014;Shang et al, 2019) and during working and episodic memory tasks Davis, Luber, Murphy, Lisanby, & Cabeza, 2017;Esslinger et al, 2014). In line with this earlier work, our connectivity analyses revealed that DLPFC stimulation before learning altered connectivity in fronto-hippocampal and striatal networks during motor sequence learning.…”
Section: Dlpfc Stimulation Influenced Connectivity In Fronto-hippocammentioning
confidence: 99%